Psikoedukasi Pencegahan Kekerasan Seksual Di SMA Tarakanita Citra Raya - HW, Astri Anggraini; Imanuel, Dastin; Rasyid, Damar; Jenica, Bunga; Audrey Orlanthia Alveria (PUSAKO : Jurnal Pengabdian Psikologi, 2025)
Sexual violence is a serious issue that has a broad impact on the physical, psychological, and social well-being of adolescents. This study aims to evaluate the effectiveness of a psychoeducational seminar in increasing students' awareness of sexual violence prevention at Tarakanita Citra Raya High School. The method used was a descriptive quantitative approach with a pre-test and post-test design without a control group. A total of 162 students participated and completed the "Children's Understanding of Sexual Violence" questionnaire before and after the seminar. The analysis showed an increase in the average score from 67.81 to 67.85, but this difference was not statistically significant. However, qualitative data from in-depth interviews with students and teachers indicated an increase in awareness, courage to refuse inappropriate treatment, and openness in discussing the issue of sexual violence. These findings indicate that the psychoeducational intervention had a positive impact qualitatively, although not yet significantly reflected in the quantitative data. Similar educational programs need to be developed in a sustainable, participatory manner, and integrated into the school curriculum to create a safe and responsive educational environment to address issues of sexual violence. Keywords: Sexual violence, psychoeducation, adolescents, prevention, sexual education in schools